Webpage ranking: how it affects your selections? - Tan, Pei Li. (2010)
Search engines have become an essential tool for interacting on the Web and they are also navigational tools that can direct users to specific Web sites or aid in browsing. However, even today‟s most successful search engines struggle to provide high-quality search results: Approximately 50 percent of Web search sessions fail to find any relevant results for the searcher.[1] This project not only helps readers to have a better understanding of how the top 4 search engines works and how they rank their pages but also shows readers method(s) to manipulate the order of displaying results. By manipulating the results, the author will be able to study the behavior of the users through proper interpretations of the testing data collected from NTU students. Such understanding may be of great help to improve search quality. One major challenge was to design programs, which was new to the author. The author‟s project will describe in full details how to design these programs using PHP, Javascript and AJAX programming language. Four methods were use to create search engines environment for students in order to collect the testing data. Due to the time constraint, the author was not able to collect testing results from the students. But instead, the author will tabulate the test results based on different scenarios and results in MySQL table to illustrate better.